(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: There is paucity of information on the effects and mechanism of action of Nanosilver on vascular tone and endothelial function in spite of the upsurge in nanotechnology application in biomedicine. The present study determined the effect of Nanosilver on vascular reactivity and endothelial function on isolated rabbit carotid artery in standard laboratory 20 mL organ bath procedures containing physiological salt solution (PSS) bubbled with 95% O2, 5% CO2. Isometric contractions were recorded electronically with a 4-channel Grass Polygraph and maintained at 37oC and pH7.4. Cumulative dose response tests to α-receptor agonist phenylephrine (PE) was examined separately, in normal PSS (control) and following 20 minutes exposure to varying concentrations of Nanosilver solution [(NAgs) (1.25 and 2.50)] μg/mL in endothelium intact (+E) (control) and endothelium denuded (-E) rings. Contractile responses were analysed with reference to maximal contractions induced by 8 x 10-2 M K+ in normal PSS. In another experiment, arterial rings were precontracted with EC70 M PE, high and /or low (8, 2 x 10-2) M K+PSS. At stable contractions, cumulative relaxation responses to NAgs was studied. Relaxation responses were analysed with reference to maximal contraction induced by EC70 M PE and/or K+ depolarization in normal PSS. Following 20 minutes exposure to NAgs, dose relaxation response to acetylcholine (ACh) was also examined in normal PSS (control), and pre-incubated L-NAME (NO synthase inhibitor) and indomethacin (cyclooxygenase inhibitor) precontracted arterial rings to further determine mechanisms of action. Data were presented as Means ± SEM. Graphs and statistical analysis were done using GraphPad prism version 7.03 and Student t-test. P-values (P< 0.05) were considered statistically significant. The results showed that nanosilver decreased maximum contraction (Emax) and induced attenuated contractile and relaxation responses concentration-dependently in +E and –E carotid arterial rings. Also, Nanosilver-induced relaxation in α- receptor mediated contraction is endothelium-dependent and showed a biphasic dose-dependent response. In conclusion, Nanosilver causes attenuation in carotid arterial smooth muscle reactivity with a biphasic dose-dependent relaxant effect and multiple endothelium-dependent pathways mode of action.